Who wants to enter teacher education, and why? The views of student teachers and secondary school students - Jónsdóttir, Halla (Icelandic Journal of Education, 2015)
This article is based on the findings of qualitative and quantitative research focusing on the views of those who entered the teacher education program at the Faculty of Teacher Education in the University of Iceland in 2009, as well as a group of students in their last year of secondary school. More precisely, the research sought to extract the participants’ views toward teacher education and compulsory school teaching. The research also examined the background of first year student teachers whose aim was to teach at grade school levels. The research was conducted in the schoolyear 2009–2010. A questionnaire was submitted to 118 students in their first year of teacher education, focusing on education in compulsory school, and to 44 secondary school students during their final year of study. In addition, focus groups were interviewed, comprising members from above-mentioned groups. The focus group was arbitrarily chosen, in total twelve student teachers and fifteen grade school students. This study is part of a comprehensive Nordic research project conducted at the behest of The Nordic Council of Ministers and simultaneously launched in five different countries: Denmark, Finland, Iceland, Norway and Sweden, under the auspices of Danmarks Evalueringsinstitut (EVA) and Danmarks Pædagogiske Universitet (DPU). The report, Rekrutteringsproblematikken på de nordiske læreruddannelser (Norræna ráðherranefndin [Nordic Council of Ministers], 2010) provides a detailed account of the central findings of the research. The current article draws on those findings as it compares the Icelandic results to those from the other Nordic countries. The findings of the research bring to light that the Icelandic student teachers comprised a relatively homogenous group; 83% women and 17% men. Here, Iceland stood out, with the highest proportion of female students in the department of compulsory school education. 98% of the secondary school students were native Icelandic speakers, the educational level of their mothers was higher than ...